PEMBENTUKAN PORTOFOLIO OPTIMAL MENGGUNAKAN MODEL INDEKS TUNGGAL - Margana, Reza Rizky; Sri Artini, Luh Gede (E-Jurnal Manajemen, 2017)
Nowadays stock investment became popular among investors and the public. Stocks are investments that have high risks. Portfolio can reduce the risk. The purpose of this study is to build an optimal portfolio using Single Index Model. This study uses LQ 45 period August 2015-January 2016 as the population. Samples were selected using census method. The analysis technique used in this study is portfolio analysis using Single Index Model. The results of this study show from 45 stocks, there are 9 shares eligible to enter the optimal portfolio include: CPIN with the proportion 12:45%, INDF with the proportion of 7.7%, HMSP with the proportion of 12.63%, GGRM with the proportion of 20.8%, PTPP with the proportion of 17.99%, SMGR with the proportion 14.98 %, with the proportion 7:16 AKRA%, TELKOM with the proportion of 3.66%, 2.63% BBTN proportions. This gives the portfolio expected return 4.87%, with a 0.01% risk level.
Keywords: LQ 45; Single Index Model; Optimal Portfolio